In vivo evidence for a cochlear amplifier in the hair-cell bundle of lizards - Manley, Geoffrey A. (The National Academy of Sciences, 2001)
Vertebrate sensory hair cells achieve high sensitivity and frequency selectivity by adding self-generated mechanical energy to low-level signals. This allows them to detect signals that are smaller than thermal molecular motion and to achieve significant resonance amplitudes and frequency selectivity despite the viscosity of the surrounding fluid. In nonmammals, a great deal of in vitro evidence indicates that the active process responsible for this amplification is intimately associated with the hair cells' transduction channels in the stereovillar bundle. Here, we provide in vivo evidence of hair-cell bundle involvement in active processes. Electrical stimulation of the inner ear of a lizard at frequencies typical for this hearing organ induced low-level otoacoustic emissions that could be modulated by low-frequency sound. The unique modulation pattern permitted the tracing of the active process involved to the stereovillar bundles of the sensory hair cells. This supports the notion that, in nonmammals, the cochlear amplifier in the hair cells is driven by a bundle motor system.